Neuroprotective Effects of Ascorbic Acid, Vanillic Acid, and Ferulic Acid in Dopaminergic Neurons of Zebrafish - Fatemeh Hedayatikatouli; Michael Kalyn; Dana Elsaid; Herman Aishi Mbesha; Marc Ekker (Biomedicines)
Background/Objectives: Parkinson’s disease (PD) is a debilitating neurodegenerative disease that targets the nigrostriatal dopaminergic (DAnergic) system residing in the human midbrain and is currently incurable. The aim of this study is to investigate the neuroprotective effects of ascorbic acid, vanillic acid, and ferulic acid in a zebrafish model of PD induced by MPTP by assessing the impact of these compounds on DAnergic neurons, focusing on gene expression, mitochondrial dynamics, and cellular stress responses. Methods/Results: Following exposure and qPCR and immunohistochemical analyses, ascorbic acid enhanced DAnergic function, indicated by an upregulation of the dopamine transporter (dat) gene and increased eGFP+ DAnergic cells, suggesting improved dopamine reuptake and neuroprotection. Ascorbic acid also positively affected mitochondrial dynamics and stress response pathways, countering MPTP-induced dysregulation. Vanillic acid only had modest, if any, neuroprotective effects on DAnergic neurons following MPTP administration. Ferulic acid exhibited the largest neuroprotective effects through the modulation of gene expression related to DAnergic neurons and mitochondrial dynamics. Conclusions: These findings suggest that ascorbic acid and ferulic acid can act as potential protective interventions for DAnergic neuron health, demonstrating various beneficial effects at the molecular and cellular levels. However, further investigation is needed to translate these results into clinical applications. This study enhances the understanding of neuroprotective strategies in neurodegenerative diseases, emphasizing the importance of considering interactions between physiological systems.